Experimental evaluation of flow distortion at tilt-rotor full-scale model air intake wind tunnel test - Habing, R.; Philipsen, I.; Muller, M.; Pecoraro, M. (My University, 2021)
Within the Clean Sky 2 Fast Rotorcraft platform, a Next Generation Civil Tilt-Rotor demonstrator is being developed. Within the related TRINIDAT project the key driving aerodynamic choices of the engine air intake configuration are being investigated. A wind tunnel model has been successfully designed and manufactured for full-scale intake testing of the basic intake configuration. The model is comprised of a nacelle, modular intake duct, rotatable spinner hub (rotor head) and wing part including deflectable aileron. In order to assess the flow quality at the Air Inlet Plane (AIP), a novel highly instrumented rotary rake has been designed. The model also includes a large amount of static pressure taps on wing and intake duct surfaces. A wind tunnel test in the DNW-LLF has been successfully performed, simulating the full flight envelope and parameter variations. The adopted scaling methodology is explained. The 6 x 6 m2 test section allowed to test the full scale model at Ma = 0.40 which is nearly cruise Mach number. The test program included a wide range of variations in angle of attack, sideslip angle, aileron deflection and suction mass-flow rate. Post-processing of the test data yielded a large database including flow distortion parameters based on the total pressure field and the velocity field in the AIP. The sensitivity of key distortion parameters to variation of model attitude, aileron deflection and mass-flow rate has been obtained for a selected set of conditions. The development of unsteady pressures along the intake duct including AIP has been characterized as well.